(untitled) (Malaysian Journal of Civil Engineering, 2018)
Most of the field problems in geotechnical engineering are in three dimensional states or close to a plane strain condition. Strength and deformation properties of soils in plane strain condition are considerably different from those in an axisymmetric condition. Many researchers have investigated the behaviour of soils under a plane strain condition. However, most of the previous studies have concentrated on sedimentary type of soils like sand and clay. Our understanding on the plane strain behaviour for residual soils is less than that for sedimentary soils. A true triaxial system with four sliding rigid-plates and real time feedback control has been used to test specimens of a completely decomposed granite (CDG) soil (a residual soil) under plane strain condition. The setup of the true-triaxial rigid plates is briefly introduced first. The preparation of soil specimens and testing procedures are described. The basic properties of the CDG are presented. The stress-strain and strength behaviour of the soil obtained under plane strain condition was investigated, and compared to the behaviour obtained under axisymmetric loading conditions. The results reveal that the critical state line in q-p′ space obtained under plane strain condition is the same as that under axisymmetric condition. However, the critical state line in e- ln p′ space obtained under undrained plane strain condition is different from that under axisymmetric condition. The peak friction angle for plane strain tests is higher than that from axisymmetric loadings. It is also found that shear bands occur only in drained plane strain compression. Defuse bulging is the mode of failure for undrained plane strain as well as triaxial loading.